Tradução, adaptação transcultural, validação e avaliação das propriedades de medida do questionário VISA-G para português brasileiro - Edson Barreto Paiva (2021)
Background: Gluteal tendinopathy is a very prevalent and disabling condition. It is essential to evaluate patients with this condition using reliable outcome measures adequately validated in the language of the targeted population. The Victorian Institute of Sports Assessment - Gluteal Tendinopathy (VISA-G) evaluates pain and function specifically in patients with gluteal tendinopathy. This questionnaire was not yet translated and cross-culturally adapted to Brazilian Portuguese, and neither had its measurement properties been investigated in Brazilian patients. Hypothesis/Purpose: translate, cross-culturally adapt and test the measurement properties of the Brazilian Portuguese version of the VISA-G. Methods: The author describes the translation procedure and validation of the Brazilian VISA-G. After a forward-backward translation protocol, the internal consistency, reliability, validity, agreement and responsiveness were tested. The responses of 68 consecutive patients on 4 questionnaires containing the VISA-G Brazil, Oswestry Disability Index, Patient Specific Functional Scale and Global Perceived Effect were used. Internal consistency was tested using the Cronbach alpha. Reliability was tested by measuring the test-retest reliability. Validity was tested by correlating the questionnaire to the other outcome measurements. Content validity was tested by measuring the floor and ceiling effects and responsiveness was tested by applying the same questionnaires to all the patients in 30 days after the initial assessment. Results: The reliability proved excellent with an intraclass coefficient of 0.91 for test-retest. Internal consistency was good (Cronbach α, .61). The construct, convergent, and divergent validities were good. The content validity was good; no floor or ceiling effect occurred. Responsiveness was 0.19. Conclusion: The validation procedure shows that the Brazilian Portuguese version of the Victorian Institute of Sports Assessment - Greater Trochanter is an valid and reliable evaluation instrument for brazilian patients with gluteal tendinopathy. Further study is necessary to evaluate its responsiveness for treatment follow-up use.